Dietary intake and risk assessment of sweeteners in prepared beverages among adolescents in Hunan province, China - HUANG Yan; XU Wenyang; YU Lan; LI Zheng; JIN Huihua (Shipin yu jixie)
ObjectiveTo verify the content of sweeteners in ready-made beverages in Hunan province, China, and the potential health risks to adolescents.MethodsTotal 850 samples of prepared beverages were collected from beverage stores across Hunan province, and the content of sweeteners in ready-made beverages was detected by high performance liquid chromatography-tandem mass spectrometry (HPLC-MS). Combined with the consumption of ready-made beverages among adolescents, the exposure levels of sodium saccharin, cyclamate and acesulfame in ready-made beverages among adolescents in Hunan province were evaluated.ResultsThe average daily exposure and P97.5 exposure of ready-made beverage cyclamate in adolescents in Hunan Province were 0.024 8 mg/kg BW (0.230% of ADI) and 0.157 0 mg/kg BW (1.430% of ADI), respectively, and the average daily exposure and P97.5 exposure of acesulfame were 0.017 6 mg/kg BW (0.120% of ADI) and 0.091 2 mg/kg BW (0.608% of ADI), respectively. The intake of sweeteners was below the safe intake value.ConclusionAt present, the dietary exposure of freshly prepared beverage sweeteners in Hunan Province poses a low risk to the health of adolescents and is at an acceptable level.